Environmental education applied to solid waste management in Frederico Westphalen, RS - Ferigollo, Isamara; Passini, Aline Ferrão Custodio; Cadore, Jéssica Stefanello; Demarco, Jessica de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Urban Solid Waste (USW) management is a highly challenging issue to be addressed in advancing sustainable urban policies. For a waste management system to be sustainable, it should be environmentally efficient, economically viable and socially accepted by the directly affected population. However, with regard to rural areas, waste management and treatment are being forgotten and consequently large amounts of waste are being inappropriately discarded, leading to serious environmental problems. In this context, this study aimed to evaluate the real situation of solid waste in the Linha São José community, located in the rural area of Frederico Westphalen city (RS, Brazil), proposing solutions for waste management and seeking the environmental awareness of the inhabitants. The methodological procedure used includes a data survey through questionnaire, in order to obtain information. Dry waste collectors were installed in the community center and environmental education campaigns were performed. The biggest issue found was the burning of dry waste which was handled by the collector implanted in the community, showing positive results for the problem. The other campaigns performed showed great importance for the waste management and an improvement in the quality of life of the community’s inhabitants.